The Relationships of Habitat Conditions, Height Level, and Geographical Position with Fruit and Seed Traits in Populations of Invasive Vine Echinocystis lobata (Cucurbitaceae) in Central and Eastern Europe - Kinga Kostrakiewicz-Gierałt; Artur Pliszko; Beata Barabasz-Krasny; Anna Bomanowska; Zygmunt Dajdok; Zigmantas Gudžinskas; Marek Kucharczyk; Łukasz Maćkowiak; Jakub Majk; Katarzyna Możdżeń; Monika Podgórska; Mindaugas Rasimavičius; et al. (Forests, 2022)
In climbing plants, fruits can be formed at different heights, depending on the height of external support. However, the effect of height on fruit and seed traits in invasive vines of Cucurbitaceae has not been intensively studied so far. In Europe, Echinocystis lobata, a North American member of Cucurbitaceae, is considered one of the most abundant invasive alien plants spreading in natural riparian forests, thickets, and tall herbs, whereas it is a rare species in urban woodlands. In this study, we tested the variability of selected fruit and seed traits of E. lobata in connection with habitat origin (natural, semi-natural, and anthropogenic), habitat type (using the EUNIS habitat classification), height (the distance between the fruit and the ground), and geographical position. The study was conducted in 2018 in 65 sites located in Latvia, Lithuania, Poland, and Slovakia. In each study site, a random sample of 10 fresh mature fruits of E. lobata was collected from subsequent 0.50 m intervals of height. The length, the width, and the weight of the fresh fruits, as well as the total number of seeds and number of undeveloped seeds per fruit, were examined. Moreover, the well-developed seeds from selected study sites were weighed. The statistical analysis showed the significant effect of habitat origin, habitat type, and height on most of the studied fruit and seed traits. The largest range of height (from 0.00 to 4.00 m) was observed in two types of habitats (F—heathland, scrub, and tundra; and G—woodland, forest, and other wooded land). The total number of seeds per fruit was positively correlated with the length, width, and weight of the fresh fruits. The fruits were a little heavier and bigger in natural habitats located in the northeast of the study area. The distribution of fruits at different heights may contribute to better dispersal of seeds by animals and wind, and may also better protect the seeds from being eaten by granivorous animals. The defence against seed-eating animals is expected to be ...